Kurkumin Memperbaiki Disfungsi Endotel Melalui Pengurangan Stres Oksidatif: Tinjauan Sistematis dan Meta-Analisis Studi Hewan - Marita Feliana; Aghnia Nurvianti Nafilah; Hendra Mahakam Putra; Marita Kaniawati; Agus Sulaeman (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Endothelial dysfunction is an early mechanism in cardiovascular disease and is closely linked to oxidative stress induced impairment of Nitric Oxide (NO) signaling. Curcumin, a bioactive polyphenol from Curcuma longa, exhibits antioxidant and vasoprotective properties. However, its mechanistic effects in preclinical models have not been quantitatively synthesized. This study evaluated the effects of curcumin on endothelial function and oxidative stress–related outcomes in animal models. A systematic search of PubMed, Embase, Scopus, and Web of Science was conducted according to PRISMA 2020 guidelines. Preclinical in vivo and ex vivo studies assessing curcumin monotherapy were included. Pooled standardized mean differences (SMDs) were calculated using a random-effects model. Risk of bias was assessed using SYRCLE, and certainty of evidence was evaluated using GRADE. Sixteen studies were included. Curcumin improved Endothelium-Dependent Vasodilation (EDV) (SMD = 1.44, 95% CI: 1.13 to 1.76, I² = 46%), increased endothelial Nitric Oxide Synthase (eNOS) expression or activity (SMD = 1.33, 95% CI: 0.75 to 1.90, I² = 68%), and enhanced NO levels (SMD = 1.15, 95% CI: 0.79 to 1.50, I² = 0%). It reduced superoxide (SMD = −2.14, 95% CI: −2.88 to −1.41, I² = 76%) and Malondialdehyde (MDA) (SMD = −1.65, 95% CI: −2.10 to −1.19, I² = 55%). Moderate to substantial heterogeneity was observed. SYRCLE indicated some concerns, and overall certainty was very low. Curcumin may ameliorates endothelial dysfunction via oxidative stress attenuation and restoration of NO signaling. However, these findings require confirmation in rigorously designed clinical studies.